Additional value of combining low-dose computed tomography to V/Q SPECT on a hybrid SPECT-CT camera for pulmonary embolism diagnosis. Issue 9 (September 2015) - Le Roux, Pierre-Yves; Robin, Philippe; Delluc, Aurélien; Abgral, Ronan; Palard, Xavier; Tissot, Valentin; Morel, Agnes; Rousset, Jean; Couturaud, Francis; le Gal, Grégoire; Salaun, Pierre-Yves
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to assess the potential interest of combining a low-dose computed tomography (ldCT) to ventilation/perfusion (V/Q) single-photon emission computed tomography (SPECT) for the diagnosis of pulmonary embolism (PE). We addressed three main questions: Could ldCT be used in substitution to ventilation SPECT? Could ldCT improve the diagnostic performance of V/Q SPECT? Could ldCT provide alternative diagnoses to PE? Methods A total of 393 patients previously analysed in a management outcome study that aimed at assessing the safety of V/Q SPECT for PE diagnosis were assessed. All patients underwent an ldCT under the same SPECT-computed tomography camera, which was not used at the time of initial interpretation. Three retrospective analyses were performed: Q SPECT combined with ldCT, V/Q SPECT combined with ldCT and ldCT only. Results On the basis of initial V/Q SPECT interpretation, 110 (28%) patients were positive and 283 (72%) were negative for PE. With Q SPECT-ldCT, 139 (35%) patients were positive and 254 (65%) were negative, with 55 (19%) discrepancies when compared with V/Q SPECT. Of the 283 patients with negative V/Q SPECT, 42 were positive with V/Q SPECT-ldCT, and among the 110 patients with positive V/Q SPECT 13 were negative with V/Q SPECT-ldCT. On using V/Q SPECT-ldCT, 97 (25%) patients were positive and 296 (75%) were negative, with 13 (3%) discrepancies when compared with V/Q SPECT (all had had a positive V/Q SPECT but a negative V/Q SPECT-ldCT). Finally, 67 (24%) ldCT scans showed a potential alternative diagnosis to PE. Conclusion For PE diagnosis with lung SPECT, the use of ldCT in substitution to ventilation SPECT is associated with a high risk of overdiagnosis. The diagnostic value of ldCT in addition to V/Q SPECT remains unclear. Further studies are needed to determine its potential role in PE diagnosis.